Prioritizing Service Quality Investments in Aesthetic Dental Clinics: An Importance-Performance Map Analysis (IPMA) Approach - Athina Isabella Sumanti; Ferdi Antonio (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This study examines the role of service quality in shaping revisit intention in private aesthetic dental services among millennials. A quantitative cross-sectional design was employed, with data collected from 241 respondents across eight accredited private dental clinics in Jakarta using an online survey. The study adopts the 6Q service quality framework and analyzes the data using Partial Least Squares Structural Equation Modeling (PLS-SEM) complemented by Importance-Performance Map Analysis (IPMA). The results indicate that technical quality has the strongest influence on revisit intention, followed by interpersonal and personnel quality. The model demonstrates substantial explanatory power, with an R² value of 0.604. IPMA findings reveal that indicators related to clinical outcomes and service efficiency, particularly aesthetic results and administrative processes, require priority improvement due to their high importance but relatively lower performance. Meanwhile, communication and clinical competence are identified as key strengths that should be maintained. These findings provide actionable insights for dental clinic managers to allocate resources more effectively by focusing on high-impact service attributes. The study contributes to the literature by extending the application of the 6Q framework in aesthetic healthcare services and integrating IPMA for more practical decision-making.